BOOK REVIEW "BRAZILIAN AUTHORITARIAN THOUGHT AND THE WORLD CRISIS", BY PAULO FAGUNDES VISENTINI - Quedi Martins, José Miguel (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2024)
Paulo Visentini’s recent work focuses on an unusual subject for an author who has already published several books on Contemporary World History and International Relations. It is a study that finds in Francisco Campos the link that connects the world crisis in the interwar period with Brazilian authoritarian thinking and the genesis of the Estado Novo. Although the author himself is the first to downplay the importance of the book - "just a youthful work" - it is a seminal work. Publishing the study 40 years later is justified by the similarities between the period analyzed and the current situation, in which the global crisis and transition are boosting authoritarian political manifestations, both nationally and globally.